2011
DOI: 10.1029/2010jb007795
|View full text |Cite
|
Sign up to set email alerts
|

Crustal structure beneath the High Lava Plains of eastern Oregon and surrounding regions from receiver function analysis

Abstract: We analyze teleseismic P‐to‐S receiver functions to image crustal structure beneath the High Lava Plains (HLP) of eastern Oregon and surrounding regions. Coverage from 206 broadband seismic stations provides the first opportunity to resolve variations in crustal composition, thickness, and heterogeneity on scales of a few km in depth and tens of km laterally across the HLP region. We utilize both H − κ stacking and a new Gaussian‐weighted common conversion point stacking technique. We find crust that is ≥40 km… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(112 citation statements)
references
References 67 publications
9
103
0
Order By: Relevance
“…In areas spanning the west coast of North America to the High Plains, these studies found specifi c tectonic provinces and terranes exhibiting structures with large variations in crustal thickness and changes in seismic velocities across the Moho (e.g., Braile et al, 1989;Prodehl and Lipman, 1989;Catchings and Mooney, 1991;Snelson et al, 1998;Bostock et al, 2002;Gorman et al, 2002;Li et al, 2002;Magnani et al, 2004;Keller et al, 2005;Frassetto et al, 2006;Lerch et al, 2007;Hansen and Dueker, 2009;Buehler and Shearer, 2010;Cox and Keller, 2010;Eagar et al, 2011;Hansen et al, 2011). Data from the Transportable Array can be used to investigate the crust across extensive distances to compare and connect the observations from these previous localized studies.…”
Section: Previous Investigationsmentioning
confidence: 97%
See 1 more Smart Citation
“…In areas spanning the west coast of North America to the High Plains, these studies found specifi c tectonic provinces and terranes exhibiting structures with large variations in crustal thickness and changes in seismic velocities across the Moho (e.g., Braile et al, 1989;Prodehl and Lipman, 1989;Catchings and Mooney, 1991;Snelson et al, 1998;Bostock et al, 2002;Gorman et al, 2002;Li et al, 2002;Magnani et al, 2004;Keller et al, 2005;Frassetto et al, 2006;Lerch et al, 2007;Hansen and Dueker, 2009;Buehler and Shearer, 2010;Cox and Keller, 2010;Eagar et al, 2011;Hansen et al, 2011). Data from the Transportable Array can be used to investigate the crust across extensive distances to compare and connect the observations from these previous localized studies.…”
Section: Previous Investigationsmentioning
confidence: 97%
“…Along the western margin of the Basin and Range, the crust thickens into the Sierra Nevada to as much as 40 km or more (e.g., Ruppert et al, 1998;Fliedner et al, 2000;Frassetto et al, 2011). Crustal thicknesses close to 40 km continue farther to the north of the Sierra Nevada into the active Cascade volcanic arc, to the east of which the crust thins in the backarc to close to 30 km within the High Lava Plains (Cox and Keller, 2010;Eagar et al, 2011).…”
Section: Previous Investigationsmentioning
confidence: 97%
“…1). This network comprised over 100 stations with most equipped with Guralp 3T or Streckheisen STS-2 broadband seismometers (Eagar et al, 2011). The second network is the USArray Transportable Array (TA) which comprises 400 broadband Streckheisen STS-2 seismometers deployed on a 70-km spaced Cartesian grid spanning an area of $2 000 000 km 2 (hollow circles in Fig.…”
Section: Acoustic-seismic Coupled Arrivals From a Surface Explosionmentioning
confidence: 99%
“…In the HLP, the time-transgressive Cenozoic volcanic activity covered the area with lava fl ows and pyroclastic material (e.g., Camp and Ross, 2004;Brueseke et al, 2007;Streck and Grunder, 2008), making it diffi cult to identify older crustal structures and decipher tectonic events (Anderson, 1989). Thus, the HLP was the focus of a large project funded by the National Science Foundation, which involved a wide range of geophysical and geological studies that helped resolve the crustal structure of the crust and upper mantle (e.g., Roth et al, 2008;West et al, 2009;Eagar et al, 2010Eagar et al, , 2011Druken et al, 2011;Cox et al, 2013).…”
Section: Introductionmentioning
confidence: 99%